(untitled) (Research, Society and Development, 2021)
This study aimed to identify what are the impacts of coronavirus on cardiac patients. This is an integrative literature review research. The search for scientific articles was carried out in the following databases: Virtual Health Library (VHL), Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SciELO) and PubMed. 7 articles were selected to compose the current study between 2020 - 2021, later discussions about the studies were elaborated. The manuscripts corroborate that cardiac patients have a higher risk of developing the severe form of COVID-19 and that these patients often end up with cardiac injuries after their recovery. It is concluded that contamination by COVID-19 aggravates damage to the heart and cardiac patients easily develop the severe form of the disease.